Changing the Band Gaps by Controlling the Distribution of Initial Particle Size to Improve the Power Factor of N‐Type Bi2Te3 Based Polycrystalline Bulks1 . Issue 8 (10th May 2017) - Zhang, Chengcheng; Fan, Xi An; Hu, Jie; Jiang, Chengpeng; Xiang, Qiusheng; Li, Guangqiang; Li, Yawei; He, Zhu
Abstract : In this work, n‐type Bi2 Te2.7 Se0.3 bulks are prepared by resistance pressure sintering technique from different particle sized powders, and the microstructure and electrical transport properties are investigated as function of the initial particle size distribution. With the initial particle size decreasing, more antisite defects, grain‐boundaries and interface defects are introduced, and lead to a larger carrier concentration due to donor‐like effect and a lower mobility due to the increasing grain boundary and carrier scattering, which results in a lower Seebeck coefficient and electrical resistivity. As a result, a maximum power factor of about 2.89 mW mK −2 at room temperature is achieved for the bulk sintered from the mix powders with different particle size distribution due to the optimization of the carrier concentration. The band gaps and the intrinsic excitation temperature are effectively adjusted by controlling the particle size in a narrow distribution. The sample sintered from the powders below 400 mesh has the highest average power factor above 2.44 mW mK −2 in the whole testing temperature range due to the improving band gaps and intrinsic excitation temperature. Abstract : By controlling the particle size in a narrow range strictly, the carrier concentration and mobility are optimized. As a result, the average PF of about 2.44 mW mK −2 is achieved in the whole testing temperature range due to the improving band gaps and intrinsic excitation temperature.